1976
DOI: 10.1152/ajplegacy.1976.231.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Digestion of tripeptides and disaccharides: relationship with brush border hydrolases

Abstract: Intestinal digestion of two tripeptides (leucyl-glycyl-glycine, prolyl-glycyl-glycine) and two disacchrarides (sucrose, maltose) was examined in the hamster by intestinal perfusion in vivo and hydrolysis of the substrates by microvillus membranes. Perfusion studies showed that luminal disappearance rates of leucyl-glycl-glycine were significantly higher than prolyl-glycyl-glycine (P less than o.001), sucrose (P less than 0.001), and maltose (P less than 0.005). Hydrolytic products of leucyl-glycyl-glycine, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

1977
1977
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Several aminopeptidases exist to reduce polypeptides, but two having broad specificities have been generalized (Danielson and Hansen, 2006). Aminopeptidase A can be credited for hydrolyzing the acidic amino acids, glutamic and aspartic acids as well as the large aliphatic and aromatic ones from the amino end of peptides while aminopeptidase N is credited with preference for the neutral ones (Arvanitakis et al, 1976;Benajiba and Maroux, 1981;Feracci et al, 1981;Matsushima et al, 1991). Such actions seem particularly favorable for release of the aliphatic-aromatic amino acids previously availed at the amino end by pepsin.…”
Section: Conducting Absorptionmentioning
confidence: 99%
“…Several aminopeptidases exist to reduce polypeptides, but two having broad specificities have been generalized (Danielson and Hansen, 2006). Aminopeptidase A can be credited for hydrolyzing the acidic amino acids, glutamic and aspartic acids as well as the large aliphatic and aromatic ones from the amino end of peptides while aminopeptidase N is credited with preference for the neutral ones (Arvanitakis et al, 1976;Benajiba and Maroux, 1981;Feracci et al, 1981;Matsushima et al, 1991). Such actions seem particularly favorable for release of the aliphatic-aromatic amino acids previously availed at the amino end by pepsin.…”
Section: Conducting Absorptionmentioning
confidence: 99%
“…Das Tripeptid Pro-Gly-Gly hingegen wird kaum durch die membrangebundenen Peptidhydrolasen gespalten, so daO fur dieses naturliche Tripeptid ein intakter Eintritt angenommen wird [33]. Daher ist auch fur diese Peptide ein Transport in intakter Form durch die luminale Plasmamembran der Enterozyten postuliert worden.…”
Section: Die Ahwrption Von Triiind Tetrapeptidenunclassified
“…Rubino et al (16), using mucosal strips in influx chambers, characterized an energy-dependent transport apparatus for peptides which could be competitively inhibited by dipeptides buit not by free amino acids. The extensive work of Matthews in animals (18) and Adibi in man (7) showed a marked advantage for amino acid absorption from small peptides over an equivalent mixture of the free amino acids and recent thorough studies of mutual inhibition between dipeptides (19) (20) and man (7) has suggested that peptides suich as Leti-Leti-Leu and LeuiGly-Gly may be hydrolyzed to a great extent before absorption since higlh concentrations of free leuicine appear in intestinal fluid simultaneously with the disappearance of the test peptide. This intraluminal accumulation of leucine couild be markedly enhanced by perfuision of isoletucine along with the leuicinecontaining tripeptide (7) stuggesting that the leucine is released at a site where it must compete withl isoleucine for the netutral amino acid transport mechanism.…”
Section: In Vivo Intestinal Perfusion Experimentsmentioning
confidence: 99%
“…In these experiments, the tetrapeptide disappeared rapidly from the test solution (20 ,umol/s per cm2 in vitro; 17 ,tmol/s per cm2 in vivo) by sequential removal of amino acid residues from the N-terminus to yield amino acids and the C-terminal dipeptide. In gut sac experiments, 61-100% of these products of hydrolysis appeared in the incubation medium and the remainder in the tissue.…”
mentioning
confidence: 95%